DEVELOPMENT OF INCLUSIVE ARCHITECTURAL DESIGN CONCEPT OF TAMAN BUNGKUL FOR PEOPLE WITH DISABILITIES - Rivaldy, Hikmal; Gunawan, Valerie Cindy; Zuhri, Syaifuddin (ADBE, 2023)
Surabaya City is a city that greatly contributes in terms of providing Green Open Space than other regions in East Java province. Bungkul Park is a form of realization of green open areas in the city of Surabaya. Facilities and infrastructure for people with disabilities really need to be considered in the accessibility of public spaces, so that they can enjoy the same rights. The Inclusive design concept is an approach that focuses on the user. In designing a public space, especially a city park, the application of inclusive architectural design is a major factor. This inclusive architectural design concept research aims to identify the quality of facilities and develop inclusive design in Taman Bungkul. This study used descriptive qualitative methods with direct surveys and assessed the level of inclusiveness of urban parks based on L Eslami’s inclusive design principles. The results showed that Taman Bungkul needed improvements in terms of accessibility advice and infrastructure for disabled users, such as ramp slopes, handwashing tubs, guide blocks, handrails and informative markers. Additional installation of barriers and rumble strips is also important to minimize the potential for accidents to visitors. In the current post- pandemic situation, public spaces need to be equipped with information about health protocols and handwashing tubs, so that people can familiarize themselves with health and hygiene.